Management of Kusuma Bhirawa Ponorogo Volleyball Club - Muhammad Alfian Lucky Jauharies; Muchsin Doewes; Slamet Riyadi (Cita Konsultindo Research Center, 2023)
Abstract This study aims to determine the Management of the Kusuma Bhirawa Ponorogo Volleyball Club, East Java Province, Indonesia. This research was carried out in October 2022. This research is a type of qualitative research. The method used in this research is survey method. Data analysis consists of four activity streams, namely: data collection, data reduction, data presentation, drawing conclusions. The conclusion of this study is that Kusuma Bhirawa's organizational structure has a clear management structure and tasks, starting from the CEO, the chairman in charge, treasurer, secretary, coach, and athletes. Athlete development Kusuma Bhirawa always coaches junior athletes and youngsters to always take part in local and higher volleyball events in order to increase the maximum match experience. The Kusuma Bhirawa training program refers to the training stages, namely the general preparation stage and the special preparation stage. Kusuma Bhirawa's coach profile is a coach who is competent in volleyball. Judging from his qualifications to enter Kusuma Bhirawa, coaches must be experienced and certified as coaches. Kusuma Bhirawa's funding comes from a single source of funds, namely dues from prospective athletes and assisted by other sponsors. Kusuma Bhirawa's training facilities and infrastructure are adequate and suitable for use by athletes and coaches in training, but unfortunately the GOR is not wide enough and the GOR floor has a little damage so that the training program is more or less optimal. Keywords: Management, Volleyball Club